Severe structural valve deterioration after TAVR with ACURATE Neo: report of two cases - Schaeffer, Thibault; Koechlin, Luca; Jeger, Raban; Leibundgut, Gregor; Reuthebuch, Oliver (Frontiers in Cardiovascular Medicine, 2023)
Structural valve deterioration (SVD) of transcatheter implanted aortic valve (TAVR) prostheses leading to prosthesis dysfunction is an uncommon yet increasingly described complication. Literature is scarce on specific mechanisms and clinical presentation of SVD after TAVR, notably on self-expanding valve ACURATE Neo. We report on two cases with severe bioprosthetic failure after ACURATE Neo implantation due to leaflet disruption, and we treated them with surgical aortic valve replacement. Based on the literature, we further discuss the incidence of SVD after TAVR, the durability of ACURATE NEO, and the modes of failure of biological valve prostheses.